Association Between Dermcidin, Salusin-?, Salusin-? Molecules and Diabetic Foot Infections - Tartar, Ayse Sagmak; Ugur, Kader; Kara, Kevser Tuncer; Akbulut, Ayhan; Demirdag, Kutbettin; Aydin, Suleyman (Sage Publications Inc, 2024)
Dermcidin, salusin-alpha, and salusin-beta are three recently discovered molecules that confer antimicrobial properties. The present study aims to investigate the association between dermcidin, salusin-alpha, and salusin-beta in the etiopathology of patients with diabetic foot infection. The study included three groups: Group 1 - diabetic foot infection; Group 2 - diabetes without history of diabetic foot; and Group 3 - the control group. Plasma dermcidin, salusin-alpha, and salusin-beta levels were compared across the groups. Median (Q1-Q3) values of plasma dermcidin levels in Groups 1, 2, and 3 were 3.45 (0.8-4.4), 5.2 (3.7-6.4), and 5.8 (3.1 -10) ng/mL, respectively. Diabetic foot infection group had significantly lower plasma dermcidin levels compared to diabetes only group and control group (P = .000, ANOVA), whereas there was no statistically significant difference between the Group 2 and Group 3 (P = . 163, ANOVA). Salusin-alpha and salusin-beta levels were significantly higher in the Group 3 compared to the other groups. Based on our findings, diabetic foot infection group had significantly lower plasma dermcidin levels and salusin-alpha and salusin-beta levels were significantly higher in the control group. These molecules (dermcidin specifically) can be researched as an adjuvant therapeutic agent in addition to conventional treatments in diabetic foot diabetic foot infections. Also, it can be searched this may prevent many complications including amputation.
Keywords: dermcidin; salusin-alpha; diabetic foot infections